Primary Antimicrobial Resistance among Helicobacter pylori Isolated in the Republic of Tatarstan in the 2008–2013 - Pozdeev O.K. (Клиническая микробиология и антимикробная химиотерапия, 2016)
This study was aimed to determine isolation rate of H. pylori from gastric mucosal biopsies in 869 patients with chronic gastritis and gastric peptic ulcers in Republic of Tatarstan during the 2008–2013. A total of 45.5% of gastric biopsy samples were positive for H. pylori. Antimicrobial susceptibility testing for H. pylori was performed by disk diffusion method. Over the study period, H. pylori isolated from patients in the both populations were susceptible to clarithromycin, amoxicillin, ciprofloxacin, and tetracycline. In 2008 and 2013, clarithromycin resistance among isolates from patients with chronic gastritis was 3.8% and 4.7%, respectively. In contrast, the only 57.4% and 37% isolates were susceptible to metronidazole. In 2008 and 2013, clarithromycin resistance among H. pylori isolated from patients with gastric peptic ulcer was 5.3% and 8.4%, respectively; metronidazole resistance was 30.3% and 24.6%, respectively